The interpretation of paganish in the philosophical and religious ideas of ukrainian philosophers of 1870s-1960s: methodological reflections - Zуnovij Timenyk (Cхід, 2017)
The object for analysis is the philosophical and theological idea of God in the structure of human, the universe and His names. The ideas of transfiguration and revelation (spiritual renewal) have also been discussed. Interpretation of paganism is based on legacy of Ukrainian thinkers (1870s-1960s), including but not limited to Sylvestr Gogotskyi, Markellin Olesnytskyi, Mykola Berdiaiev, Serhii Bulhakov, and Vasyl Zinkivskyi.